INCLUSION OF BLIND CHILDREN IN THE SCHOOL ENVIRONMENT: CHALLENGES AND STRATEGIES - Rocha Lopes, Juliana; Rafaela Costa Carmona, Ana; Cristina Aparecida Licurgo da Fonseca, Ana; Regina da Silva, Tânia; de Souza Oliveira Almeida, Renata; Silva de Lima, Bárbara; Pereira Gusmão, Jaqueline; Paula Bosch, Ana; Gabriela Ferreira, Thais; Oliveira da Silva, Patrícia (Revista Gênero e Interdisciplinaridade, 2025)
The inclusion of blind children in the school environment is a complex process that goes beyond the pedagogical realm, encompassing social, cultural, and emotional dimensions. Although Brazilian legislation guarantees the right to inclusive education, barriers still persist that compromise the effectiveness of this policy. This article aims to analyze the main challenges faced by blind children in the school context and discuss strategies that promote their learning and socialization, based on theoretical frameworks, legislation, and case studies. The results indicate that overcoming these barriers depends on ongoing teacher training, curricular adaptation, and raising awareness within the school community.